Spina Bifida - A descriptive research study - D.L. Bonnes (AOSIS, 1985)
In society one is continually being made aware of the needs and demands of the physically or mentally handicapped child. This awareness is stimulated by the media, medical journals as well as the general public's own increased interest in the children's plight.